A Data Warehouse Architecture Model for Al-Quds Open University - Taha, Ashraf M. (2006)
Data warehousing is important, not only in business enterprises, but in the university environment as well. The goal of a data warehouse is to integrate timely, accurate information and to make it available to an organization's employees and decision makers. The data warehouse is developing in response to increasing data and information requirements. The traditional notion of data warehouses is evolving into a federated warehouse augmented by a set of processes and services to support integrated and consistent access to heterogeneous, decentralized warehouse systems. This study will explore the design and implementation of a data warehouse architecture model for the Al-Quds Open University (QOU) in Palestine, within the Context of Relational Online Analytical Processing (OLAP). The model aims at integrating data from different sources in the QOU.